Tanah Lot temple: Navigating the tension between tourism development and cultural preservation - Sinaga, Firman; Kanca, I Nyoman; Suarja, I Ketut (Journal of Commerce, Management, and Tourism Studies, 2025)
The development of Tanah Lot Temple as a prominent tourist destination in Bali has significantly influenced the region’s economic, social, and environmental dynamics. This study aims to examine these impacts by analyzing the economic contributions of tourism, the social transformations experienced by local communities, and the environmental challenges arising from increased visitation. Additionally, the study seeks to propose sustainable tourism strategies that balance economic growth with cultural and environmental preservation. This research employs a qualitative approach, utilizing interviews and observations to gather data from visitors, local businesses, and community members. Interviews focus on perceptions regarding tourism’s economic benefits, cultural shifts, and environmental concerns. Observations are conducted at the site to assess visitor behavior, infrastructure conditions, and environmental changes. The collected data are analyzed thematically to identify key trends and perspectives. The findings reveal that tourism at Tanah Lot Temple significantly contributes to the local economy, particularly in trade, hospitality, and services. However, the rapid growth of tourism has also introduced several challenges. Socially, the local community faces a dilemma between preserving cultural heritage and adapting to commercial tourism demands. While many residents take pride in the temple’s global recognition, concerns about cultural erosion and over-commercialization persist. Environmentally, issues such as waste management, congestion, and land degradation emphasize the need for sustainable management. In conclusion, while Tanah Lot Temple’s tourism industry generates substantial economic benefits, addressing the associated social and environmental challenges is crucial for long-term sustainability. Effective infrastructure management, active community involvement in decision-making, and the adoption of eco-friendly tourism practices are essential strategies. By integrating these approaches, Tanah Lot Temple can continue to thrive as a responsible and sustainable tourist destination that preserves its cultural and environmental integrity.